Автоматизований моніторинг для виявлення потенційно небезпечних ситуацій під час роботи з навантажувачами на виробничих підприємствах - Зінченко, Д. О. (ХНУРЕ, 2024)
This work is devoted to safety issues when working with a forklift. This transport has become widely used in loading and unloading processes, but this type of activity is dangerous for the life of the operator and others. The monitoring system is considered as a tool that can solve the problem. A brief description of the features of the solution implementation is provided. OpenCV is considered as a technology to implement such a monitoring system.
Keywords: автоматизований моніторинг; виробничі підприємства; навантажувачі; технологія OpenCV